Anser to new challenges: University 360 - P. P. Ivanov; G. M. Parnikova (Вестник Северо-Кавказского федерального университета)
The purpose of the article is to present the main ideas and concepts of «University 360», implemented as a part of the digital transformation track of the university. It is a part of the North-Eastern Federal University’s Digital Ecosystem strategic development program. Tangible forecast results of the project «University 360» for the domestic system of higher education: a significant increase in the contingent of students; creation of fundamentally new systems for supporting and implementing individual educational trajectories for the development of students; ensuring the quality of higher education by creating conditions for personalization and customization of training; the inclusion of fundamental higher education in the human life cycle circuit; maximizing the potential of students.